2019
DOI: 10.1038/s41589-019-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

MCC950 directly targets the NLRP3 ATP-hydrolysis motif for inflammasome inhibition

Abstract: Inhibition of the NLRP3 inflammasome is a promising strategy for the development of new treatments for inflammatory diseases. MCC950 is a potent and specific small-molecule inhibitor of the NLRP3 pathway, but its molecular target is not defined. Here we show that MCC950 directly interacts with the Walker B motif within the NLRP3 NACHT domain, thereby blocking ATP hydrolysis and inhibiting NLRP3 activation and inflammasome formation. Main Text: The NOD-like receptor (NLR) family, pyrin domain-containing protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
500
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 691 publications
(519 citation statements)
references
References 31 publications
17
500
0
2
Order By: Relevance
“…As a priming signal, we showed that either incubation of macrophages or intranasal treatment of mouse with ESAT-6 induced pro-IL-1β expression, consistent with our previous reports that ESAT-6 stimulates macrophage production of inflammatory cytokine and chemokine (19, 38). As an activation signal, our data with MCC950, a novel selective NLRP3 inhibitor (23, 24), showed that Mtb stimulates mature IL-1β production by macrophages in an NLRP3 dependent manner, consistent with the previous study [16]. We have also shown previously with human monocyte derived dendritic cells that caspase-1 is required for ESAT-6 mediated production of IL-1β (20).…”
Section: Discussionsupporting
confidence: 91%
“…As a priming signal, we showed that either incubation of macrophages or intranasal treatment of mouse with ESAT-6 induced pro-IL-1β expression, consistent with our previous reports that ESAT-6 stimulates macrophage production of inflammatory cytokine and chemokine (19, 38). As an activation signal, our data with MCC950, a novel selective NLRP3 inhibitor (23, 24), showed that Mtb stimulates mature IL-1β production by macrophages in an NLRP3 dependent manner, consistent with the previous study [16]. We have also shown previously with human monocyte derived dendritic cells that caspase-1 is required for ESAT-6 mediated production of IL-1β (20).…”
Section: Discussionsupporting
confidence: 91%
“…The compound MCC950 (also known as CRID3) is the NLRP3 inhibitor that has been the most studied to date . MCC950 inhibits NLRP3 by directly interacting with the NLRP3 ATPase domain, thereby blocking ATP hydrolysis and NLRP3 oligomerization .…”
Section: Inflammasome‐targeted Therapies In Arthritic Diseasesmentioning
confidence: 99%
“…The compound MCC950 (also known as CRID3) is the NLRP3 inhibitor that has been the most studied to date . MCC950 inhibits NLRP3 by directly interacting with the NLRP3 ATPase domain, thereby blocking ATP hydrolysis and NLRP3 oligomerization . Several studies have shown therapeutic efficacy of MCC950 in a variety of preclinical mouse models, including atherosclerosis, experimental autoimmune encephalomyelitis, diabetes, steatohepatitis, and colitis .…”
Section: Inflammasome‐targeted Therapies In Arthritic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…113 The NLRP3 inflammasome induces neuroinflammation and drives PD pathogenesis, as murine models of PD are protected from disease by Nlrp3 deficiency or dosing with MCC950, 38 a small-molecule NLRP3 inhibitor. 114,115 Excitingly, MCC950 suppressed disease in a murine model of PD in which dopaminergic neurons are deficient in TFAM (MitoPark model). 38 This highlights NLRP3 inhibition as a promising therapeutic strategy for the treatment of PD and other diseases involving mitochondrial dysfunction.…”
Section: Mitochondrial Disruption and Nlrp3 Inflammasome Activity Inmentioning
confidence: 99%